Swelling and Erosion Modulation of Sterculia Foetida Gum Through Real Time Texture Probing - Namdeo, Bendgude; Vidya, Iyer; Sushilkumar, Poddar (Dhaka University Journal of Pharmaceutical Sciences, 2009)
In the present investigation an attempt has been made to increase therapeutic efficacy, reduce frequency of administration and improve patient compliance by developing controlled release matrix tablets of diltiazem hydrochloride. Diltiazem hydrochloride was formulated as oral controlled release matrix tablets by using sterculia foetida gum. SFG fines were characterized with scanning electron microscopy. The purpose of this study was to optimize release profile of the highly water soluble drug from SFG matrix by using water soluble and swellable excipients like lactose and microcrystalline cellulose respectively. Tablets were prepared by direct compression, and their swelling behavior in presence of these excipients was assessed with the help of a Texture Analyzer. Dissolution assessment was performed using USP 26 apparatus 2 modified by insertion of a mesh to prevent sticking of the tablets to the bottom of vessel and allow them to swell three dimensionally. The interdependence of swelling front movement in relation to excipients type and progression of drug release are explained. It was concluded that unlike in conventional dosage forms insertion of excipients in hydrophilic controlled release tablets containing a water soluble drug gave the finger print information of drug release profile. In vitro drug release from these matrices was characterized and confirmed with the help of real time texture probing. Results indicated that it is possible to achieve desired modulation in the drug release profile by inclusion of lactose and microcrystalline cellulose. Key words: Diltiazem HCl, Sterculia Foetida Gum, Swelling and erosion, Lactose, Texture analysis. doi: 10.3329/dujps.v7i2.2167 Dhaka Univ. J. Pharm. Sci. 7(2): 127-132, 2008 (December)